Summary of Gridding-based Planning Method for Electric Energy Substitution Supporting Network. Issue 1 (February 2021) - Li, Yaxin; Yang, Jie; Fang, Rengcun; Xu, Hanping; Yang, Ruixi; Zhang, Dongyin
Abstract: Electric energy substitution technology is of great significance for optimizing the final energy consumption structure, promoting energy conservation and emission reduction, and preventing air pollution. This paper aims to review the current research status of electric energy substitution technology and related fields, summarize the planning methods of electric energy substitution supporting network, and provide reliable network support for large-scale promotion of electric energy substitution. Firstly, the connotation, strategic significance and characteristics of electric energy substitution technology are summarized, and the basic structure of electric energy substitution technology is proposed. Then, the characteristics of network planning and gridding planning ideas are integrated into the gridding planning framework under the background of electric energy substitution is proposed. Finally, the development challenges of gridding planning methods in the current electric energy substitution background in terms of technology, mechanism and infrastructure are summarized, and looking forward to the development direction of the electric energy replacement supporting network plan under the background of the 14th Five-Year Plan and the new round of power system reform.